Pelatihan Praktis Manajemen Waktu dan Prioritas untuk Meningkatkan Efisiensi Belajar Siswa MT’S Riyadul Fallah Pabuaran Kecamatan Sukamakmur Kabupaten Bogor - Afrizal Afrizal (Jurnal Abdimas Indonesia, 2026)
This community service program aims to improve students' ability to manage time effectively to enhance learning achievement. Time management is an essential skill that students must master to balance academic activities, extracurricular activities, and personal life. However, many students experience difficulties in organizing their study time, which impacts declining academic performance and increasing stress levels. Through this activity, students are given an understanding of time management concepts, activity planning techniques, task prioritization, and strategies to overcome procrastination. The results show that participants have a better understanding of the importance of time management and how to apply it in daily life. Students have become more skilled in creating structured study schedules, setting task priorities, and utilizing free time productively. In addition, students also showed increased awareness of the negative impacts of procrastination and have strategies to overcome it. Overall, this community service program contributes to helping students optimize their study time to achieve better academic performance